Improving child health promotion practices in multiple sectors - outcomes of the Swedish Salut Programme - Edvardsson Kristina; Ivarsson Anneli; Garvare Rickard; Eurenius Eva; Lindkvist Marie; Mogren Ingrid; Small Rhonda; Nyström Monica E (BMC, 2012)
Abstract Background To improve health in the population, public health interventions must be successfully implemented within organisations, requiring behaviour change in health service providers as well as in the target population group. Such behavioural change is seldom easily achieved. The purpose of this study was to examine the outcomes of a child health promotion programme (The Salut Programme) on professionals' self-reported health promotion practices, and to investigate perceived facilitators and barriers for programme implementation. Methods A before-and-after design was used to measure programme outcomes, and qualitative data on implementation facilitators and barriers were collected on two occasions during the implementation process. The sample included professionals in antenatal care, child health care, dental services and open pre-schools (n=144 pre-implementation) in 13 out of 15 municipalities in a Swedish county. Response rates ranged between 81% and 96% at the four measurement points. Results Self-reported health promotion practices and collaboration were improved in all sectors at follow up. Significant changes included: 1) an increase in the extent to which midwives in antenatal care raised issues related to men's violence against women, 2) an increase in the extent to which several lifestyle topics were raised with parents/clients in child health care and dental services, 3) an increased use of motivational interviewing (MI) and separate 'fathers visits' in child health care 4) improvements in the supply of healthy snacks and beverages in open pre-schools and 5) increased collaboration between sectors. Main facilitators for programme implementation included cross-sectoral collaboration and sector-specific work manuals/questionnaires for use as support in everyday practice. Main barriers included high workload, and shortage of time and staff. Conclusion This multisectoral programme for health promotion, based on sector-specific intervention packages developed and tested by end users, and introduced via interactive multisectoral seminars, shows potential for improving health promotion practices and collaboration across sectors. Consideration of the key facilitators and barriers for programme implementation as highlighted in this study can inform future improvement efforts.